Peran Etika Bisnis dalam Meningkatkan Loyalitas Konsumen: (Studi Kasus pada Produk UMKM Bolu Kembojo di Kota Dumai) - Andi Riski Firnanda; Hildawati Hildawati (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
The development of Micro, Small, and Medium Enterprises (MSMEs) in the traditional culinary sector in Dumai City has shown significant growth, particularly in bolu kembojo products. Increasing competition requires business actors not only to focus on product quality but also to implement business ethics in their operations. This study aims to analyze the role of business ethics in enhancing customer loyalty toward bolu kembojo MSME products in Dumai City. This research employs a qualitative approach using a case study method, with informants consisting of MSME owners and consumers selected purposively. Data collection techniques include interviews, observations, and documentation, while data analysis is conducted using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that the implementation of business ethics, such as honesty, responsibility, and good service, can enhance customer trust and satisfaction. These factors subsequently encourage repeat purchases and positive word-of-mouth recommendations. The implication of this study suggests that the application of business ethics is a crucial strategy for MSMEs in strengthening customer loyalty and sustaining business continuity.